Group Counseling With Traditional Malay Riau Game Techniques In Implementing The Pancasila Student Profile - Donal, Donal; Mariah, Kiki; Munawir, Munawir; Ramadhani, Erfan (Educational Guidance and Counseling Development Journal, 2025)
The cultivation of the Pancasila Student Profile is inseparable from the role of Guidance and Counseling (GC) teachers in schools. GC teachers function to help develop students' potential, including instilling the values of the Pancasila Student Profile. Group counseling serves as an effort to provide assistance in student development using Traditional Malay Riau game techniques. This study aims to determine the effectiveness of Traditional Malay Riau Game Techniques in implementing the Pancasila Student Profile. This research employs a quantitative approach with a quasi-experimental design. The sampling technique used is purposive sampling, with the primary criterion being individuals with a low application of the Pancasila Student Profile. The findings indicate that the Traditional Malay Riau Game Techniques in group counseling show significant effectiveness in enhancing the implementation of the Pancasila Student Profile among junior high school students. Games such as congklak, lulu cina buta, and statak not only serve as a means of entertainment but also function as educational tools that foster students' character, such as cooperation, independence, and critical thinking.